Closed Die Deformation Behavior of Cylindrical Iron–Alumina Metal Matrix Composites During Cold Sinter Forging - Prasanna Kumar U.J.; Gupta P.; Jha A.K.; Kumar D. (My University, 2025)
The present paper aims to study the closed die deformation behavior of cylindrical Fe–Al2O3 metal matrix composites (MMCs). Closed die was manufactured by machining the high carbon steel block followed by oil quenching and then finishing. Samples sintered at a temperature of 1100 °C for 1 h were characterized with X-ray diffraction and scanning electron microscopy, which showed the formation of Fe, Al2O3 and nano size FeAl2O4 phases respectively. Density and hardness of the composite samples were determined after sintering. Closed die deformation studies of the prepared composite samples were carried under three different interfacial frictional conditions i.e. dry, solid lubricating and liquid lubricating. Hardness, density and metallographic characterizations were also done for the deformed samples. On comparing the micrographs of the samples before and after deformation it was revealed that in deformed specimens recrystallization has taken place due to the difference in the energy between the strained iron matrix and unstrained alumina reinforcement during closed die forging process. Experimental density of the samples was also verified with the theoretical density using the standard equations. It is expected that the results of the present investigations will be helpful in developing quality MMC components for wide industrial applications. © 2015, The Institution of Engineers (India).